Genomic features specific to the human lineage are associated with neurological diseases and intelligence. Issue 6 (27th May 2022) - Chen, Zhongbo; Zhang, David; Reynolds, Regina; Gustavsson, Emil; Ruiz, Sonia Garcia; Hardy, John; Houlden, Henry; Taliun, Sarah Gagliano; Botia, Juan; Ryten, Mina
Abstract : While encephalisation has provided advantages to human evolution, it may have also predisposed us to neurological diseases as common neurodegenerative disorders such as Alzheimer's and Parkinson's disease do not occur naturally in aged non-human primates. Thus, human lineage-specific genomic features may provide insights into brain-related diseases. We leveraged high-depth whole genome sequencing data to generate a novel annotation that identifies genomic regions specific to humans and not conserved within non-human primates (termed constrained, non-conserved regions; CNCRs). We proposed that these regions have been subject to human-specific purifying selection and are enriched for brain-specific elements, relevant to human-specific disease. We found that CNCRs are depleted from protein-coding genes but enriched within the non-coding genome. Per-SNP heritability of a range of brain-relevant phenotypes are enriched within CNCRs including intelligence, Parkinson's disease and schizophrenia. We found that genes implicated in neurological diseases have high CNCR density, in par- ticular: APOE, highlighting an unannotated intron-3 retention event. Using human brain RNA-sequencing data, we showed this human-specific intron-3-retaining transcript to be more abundant in Alzheimer's disease with more severe tau and amyloid pathological burden. Thus, we demonstrate the importance of human-lineage-specific genomic sequences in neurological disease and make this information available in a public platform online. zhongbo: chen@ucl.ac.uk 18